Parauapebas in two times:: theoretical perspectives and empirical evidence from a professor-researcher - Kzam, Athila Lima (Geografares, 2022)
This is a brief private exposition of a research trail that brings together a bibliographic review, exploratory fieldwork and semi-structured interviews carried out in Parauapebas, southeast of the Pará state, with an interval of 15 years between them. The report exposes impressions and reflections that were developed based on theoretical perspectives and empirical evidence of this portion of the Amazonian geographic space, heavily influenced by mining in Serra dos Carajás.